Challenges and coping strategies of U.P. Diliman VAAS Awardees - Superficial, Alena V.; Tongson, Excelsa C. (2010.)
ABSTRACT The study identified and described the challenges encountered and the coping strategies employed by the University of the Philippines, Diliman VAAS awardees. Furthermore, it determined the similarities and differences in gender in terms of coping strategies, family influence, and types of family support. Fifty VAAS awardees from each gender, enrolled in the Second Semester 2009-2010 were randomly selected to participate in the survey while five males and five females participated in Focus Group Discussions. Data obtained from the survey were analyzed using frequency and percentages while data from FGDs were grouped into themes. Results indicated seven themes for the challenges for both gender such as academic-related challenges, competing time concerns, decision-making difficulties, emotional and mental strain, physical pain and exhaustion, financial constraints, and personal drive and motivation struggles. Both males and females employed a variety of coping strategies. However, it was noted that some VAAS awardees do not employ any coping strategies. The family is the primary supporter who provides both financial and morale support to the VAAS awardees. The study recommended creating programs that will equip the VAAS awardees in coping better with challenges. Future studies may look into the challenges and coping strategies of freshmen VAAS awardees.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: College athletes -- Philippines; University of the Philippines -- Sports